Rethinking Wali Mujbir In Islamic Family Law: Maqasid Al-Shariah, Gender Justice, And Legal Reform - Ramza Fatria Maulana; Mesraini Mesraini; Asmawi Asmawi; Khairul Amin; Zulkifli Dahrial (Universitas Muhammadiyah Bandung, 2025)
The phenomenon of forced marriage remains a critical issue in Indonesian society, especially considering the high rate of child marriage, which is often legitimized by the concept of wali mujbir. In classical Islamic law, the wali mujbir is granted the right of ijbār to marry a girl without her consent, a practice that is considered a form of protection. However, in the contemporary context, this practice is increasingly questioned because it is contrary to the principles of gender equality, human rights, and maqāṣid shari'ah. This study shows that forced marriage by a guardian without the consent of a woman has the potential to create mafsadat, such as household disharmony and violation of individual autonomy. From the perspective of maqāṣid syarī'ah, marriage must ensure the public interest, justice, and individual freedom. Countries such as Indonesia have abolished the right of guardians to force marriage through regulations, such as Law No. 1 of 1974 and KHI. The recontextualization of the guardian mujbir is needed to shift the role of the guardian from a coercive authority to a companion who ensures the public interest.